2004
DOI: 10.1080/13651500310004506
|View full text |Cite
|
Sign up to set email alerts
|

Does having offspring reduce the risk of suicide in women?

Abstract: The protective effect offspring confer on their mother against suicide appears to operate so long as the offspring lives at home irrespective of off spring's age. The protective effect appears to be lost once they leave home. These findings are discussed in the context of the kin selection hypothesis and deCatanzaro's Darwinian hypothesis on human suicide. (Int J Psych Clin Pract 2004; 8: 25-29).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Unlike the minimum wage, the EITC primarily targets families with dependent children. While our data does not include information about the presence of children, studies suggest that the presence of minor children reduces the risk of suicide (Driver and Abed 2004;Denney 2010). Such a pattern would be consistent with smaller and noisier effects of the EITC relative to the effects of the minimum wage.…”
Section: Event Studiesmentioning
confidence: 99%
“…Unlike the minimum wage, the EITC primarily targets families with dependent children. While our data does not include information about the presence of children, studies suggest that the presence of minor children reduces the risk of suicide (Driver and Abed 2004;Denney 2010). Such a pattern would be consistent with smaller and noisier effects of the EITC relative to the effects of the minimum wage.…”
Section: Event Studiesmentioning
confidence: 99%
“…When considering protective factors, this study highlighted that the perceived sense of other's loss can prevent suicide attempts, especially when children are involved (46,47). Using personal strengths during difficult times has been found to improve self-worth within depressed and non-depressed TBI populations, leading to the reduction of suicidal ideations and attempts (48).…”
Section: Discussionmentioning
confidence: 99%
“…Psychotropic medication was included in the hypothesized model because previous research has shown that receiving medication is associated with suffering comorbid depressive disorders and more frequent use of mental health services (Harpaz-Rotem, Rosenheck, Mohamed, & Desai, 2009;Mohamed & Rosenheck, 2008). Finally, it has been found that a number of demographic factors (e.g., being female, younger, unmarried or divorced/widowed, having dependent children) are predictive of increased suicidal thoughts and behaviors in the general population (e.g., Bernal et al, 2006;Driver & Abed, 2004;Kessler, Borges, & Walters, 1999).…”
mentioning
confidence: 94%